Chest compression of a pregnant woman by a seatbelt might affect fetal outcome, even in minor to moderate frontal vehicle collisions. (September 2019) - Ishiko, Akiko; Hitosugi, Masahito; Takaso, Marin; Mizuno, Koji; Tsuji, Shunichiro; Ono, Tetsuo; Kimura, Fuminori; Murakami, Takashi
Highlights: Frontal vehicle crash was simulated using a dummy which represents a pregnant woman. Restrained pregnant woman's kinematics was analyzed at a velocity of ≤40 km/h. If the seatbelt is correctly used, a maximum chest deflection of 35.4 mm was observed. Subsequent forces might be applied on the uterus. Negative fetal outcomes are partly owing to chest compression. Abstract: Introduction: Pregnant women often suffer from negative fetal outcomes, despite wearing a seatbelt correctly. When restrained vehicle passengers are involved in a frontal collision without suffering from any injuries, the forces they experience are particularly concentrated in the chest because of the seatbelt. We analyzed the biomechanics of chest injuries sustained by restrained pregnant drivers and possible effects of these injuries on the fetus. Material and methods: The Maternal Anthropometric Measurement Apparatus dummy, version 2B, representing a pregnant woman at 30 weeks of gestation, was used. Sled tests were performed for recreating frontal impact situations with vector velocity changes at impact speeds of 13, 26, and 40 km/h. Overall kinematics of the dummy were examined using high-speed video imaging. Quantitative dummy responses, such as time course of acceleration of the sled and chest, pressure of the belt, and deflection of the chest (right and left) during impact were also measured. Results: Although collision velocities were different, the distances of forward movement of the dummy were similar (121–129 mm) owing to the safety devices. However, maximum deflection of the chest (35.4 mm to the left and 15.7 mm to the right) was obtained at a 26-km/h collision. Additionally, maximum deflection of 28.7 mm to the left and 10.9 mm to the right of the chest were obtained at 40 km/h. Conclusions: Because the uterus enlarges and the fundus reaches the lower part of the rib cage during late pregnancy, we consider that the reason for negative fetal outcomes is partly owing to chest compression and subsequent applied forces on the uterus, even in minor to moderate frontal collisions. This knowledge may be useful for forensic scientists who determine the causes and mechanisms of a fetal death or the offenders' responsibilities for both maternal and fetal outcomes when the mother is involved in a frontal vehicle collision.